Risk Assessment of Personal Care Products, Pharmaceuticals, and Stimulants in Mgeni and Msunduzi Rivers, KwaZulu-Natal, South Africa - Gumbi, Bhekumuzi P.; Moodley, Brenda; Birungi, Grace; Ndungu, Patrick G. (Frontiers in Water, 2022)
In this work, environmental occurrence and risk assessment of pharmaceuticals, personal care products (PPCPs), and stimulants are presented. A quantitative technique is described for ultrasonic-assisted solid-phase extraction (SPE) followed by GC-MS after derivatization of PPCPs; propylparaben, triclosan, carbamazepine, chloramphenicol, and stimulant caffeine. Ultrasonic-assisted extraction together with centrifugation were used to extract sediment samples collected from the Mgeni and Msunduzi rivers. An SPE procedure was used for cleanup and to concentrate selected compounds from diluted aqueous extracts. The final extracts were derivatized and analyzed with GC-MS in selected ion monitoring (SIM) mode. The recoveries of the analytes ranged from 66 to 108%. The method detection limits were (0.08–1.82 ng g−1 for solid and 0.08–10 μg L−1 for liquid) and quantification limits (0.42–5.51 ng g−1 for solid and 0.25–25 μg L−1 for liquid). The optimized method was applied in the evaluation of two rivers over 3 months in KwaZulu-Natal, South Africa. All targeted compounds were present in the environment at concentration levels between not detected to 174 ng g−1 and not detected to 30 μg L−1 for solids and aqueous environmental samples, respectively. A comparison of predicted no environmental effect concentration (PNECs) with measured environmental concentration (MECs) showed that these PPCPs present a high ecological risk to the receiving environment (agricultural lands and households). Our work is close to reality because we used MECs as opposed to using predicted environmental concentration (PECs) values, which are normally calculated from consumption, production of compound per year, and various estimated factors.